The Effect of Deferred Tax and Tax To Book Ratio on the Company's Financial Performance: Pengaruh Pajak Tangguhan dan Tax To Book Ratio Terhadap Kinerja Keuangan Perusahaan - Amaliyah, Afik; Ernandi, Herman (Indonesian Journal of Law and Economics Review, 2018)
This study aims to determine the effect of Deferred Taxes and Tax to Book Ratio on Corporate Financial Performance in chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) either partially or simultaneously. This study uses quantitative data with secondary data collection techniques. The population in this study is the chemical sub-sector companies listed on the Indonesia Stock Exchange from 2012 to 2016. While the sample of this study was determined by purposive sampling method and obtained 10 sample companies. The analytical method used is multiple linear regression analysis. Based on the results of this study, the results of (1) Deferred Tax have an effect on the Company's Financial Performance, with the results of the t test amounting to 0.014. (2) Tax to Book Ratio affects the Company's Financial Performance, with the results of the t test equal to 0.008. (3) and deferred tax and tax to book ratio have a significant effect on the company's financial performance with the results of the F statistic test of 0.001.